Does the presence of scrapie affect the ability of current statutory discriminatory tests to detect the presence of BSE? - Simmons, M.M.; Chaplin, M.J.; Vickery, C.M.; Simon, S.; Davis, L.; Denyer, M.; Lockey, R.; Stack, M.J.; O'Connor, M.J.; Bishop, Keith; Gough, Kevin C.; Maddison, Ben C.; et al. (American Society for Microbiology, 2015)
Current European Commission (EC) surveillance regulations require discriminatory testing of all transmissible spongiform encephalopathy (TSE)-positive small ruminant (SR) samples in order to classify them as bovine spongiform encephalopathy (BSE) or non-BSE. This requires a range of tests, including characterization by bioassay in mouse models. Since 2005, naturally occurring BSE has been identified in two goats. It has also been demonstrated that more than one distinct TSE strain can coinfect a single animal in natural field situations. This study assesses the ability of the statutory methods as listed in the regulation to identify BSE in a blinded series of brain samples, in which ovine BSE and distinct isolates of scrapie are mixed at various ratios ranging from 99% to 1%. Additionally, these current statutory tests were compared with a new in vitro discriminatory method, which uses serial protein misfolding cyclic amplification (sPMCA). Western blotting consistently detected 50% BSE within a mixture, but at higher dilutions it had variable success. The enzyme-linked immunosorbent assay (ELISA) method consistently detected BSE only when it was present as 99% of the mixture, with variable success at higher dilutions. Bioassay and sPMCA reported BSE in all samples where it was present, down to 1%. sPMCA also consistently detected the presence of BSE in mixtures at 0.1%. While bioassay is the only validated method that allows comprehensive phenotypic characterization of an unknown TSE isolate, the sPMCA assay appears to offer a fast and cost-effective alternative for the screening of unknown isolates when the purpose of the investigation was solely to determine the presence or absence of BSE.